Fact-checking governamental: controle da informação e propaganda na agência de checagem do Governo do Ceará - Costa, Rômulo Almeida da (2024)
This research aims to understand the normative shifts of fact-checking when it is incorporated as a government communication strategy in the state's attempt to regain control of information of the digital platforms (VALENTE, 2019) and the use of disinformation as a political practice (LELO, 2019). Our analysis focuses on the Antifake CE agency, launched by the Government of Ceará in 2019. We start from the Political Economy of Communication to understand the power struggles over information and their impact on the reconfiguration of the public sphere by TICs (BOLAÑO, 2000) specially the internet. In this context we also discuss the political aspects of disinformation on the web and the role of the state dealing with the problem. We use the concept of government communication (BRANDÃO, 2009), in contrast to public communication (DUARTE, 2011) and discuss the role of propaganda (WEBER, 2011) as a strategy of persuasion and domination by the state. The study of a hybrid nature consists of analyzing 45 fact-checks published between 2020 and 2022 during the administration of Governor Camilo Santana (PT-CE) with the intention of identifying deviations from the normative practice of fact-checking and expressions of the political dispute in the official publications. Initially, we carried out a Content Analysis (SAMPAIO; LYCARIÃO, 2021) based on categories that identify aspects of the institutional approach and the production of the government agency. We carried out a Critical Discourse Analysis (FAIRCLOUGH, 2001) in order to identify the ways of eash ideology operation (THOMPSON, 2011) in the agency's texts. The results indicate that Antifake CE is part of the state government's strategic communication to position itself on issues of political dispute and rebut accusations from opponents acting in terms of the propaganda function with an emphasis on legitimizing the official discourse maintaining the state's control of information and defending the government's political-institutional image.